The sound recording and archive from the standpoints of ethnomusicology - García, Miguel A. (Revista General de Información y Documentación, 2019)
The article proposes a journey along the different ways in which ethnomusicology hasreflected on the sound recording and archive, from its first formulation, known as comparativemusicology, to the present day. The journey reveals that the discipline has selectively adoptedquestions, definitions and concepts from other areas of knowledge, and that its reflections on thesound recording and archive have been sensitive to the theoretical, ethical and methodologicalchanges, which have taken place inside the discipline. It also confirms that in the current reflectionscenario on the subject very different perspectives coexist, some of them adopted over a century ago,which define the archive as an institution, reservoir, memory and/or knowledge.
Keywords: Sound recording; Sound archive; Ethnomusicology; Archives and postmodern theory; Archival sciences; Epistemology of archive